DTwP-HB-Hib: antibody persistence after a primary series, immune response and safety after a booster dose in children 18-24 months old - Hartono Gunardi; Kusnandi Rusmil; Eddy Fadlyana; Soedjatmiko; Meita Dhamayanti; Rini Sekartini; Rodman Tarigan; Hindra Irawan Satari; Bernie Endyarni Medise; Rini Mulia Sari; Novilia Sjafri Bachtiar; Cissy B. Kartasasmita; et al. (BMC, 2018)
Abstract Background The new combination of DTwP-HB-Hib vaccines has been developed in Indonesia following World Health Organization (WHO) recommendation and integrated into national immunization program. The aims of the study were to measure 1) antibody persistence 12-18 months after a primary series, 2) immune response and safety after a booster dose of DTwP-HB-Hib. Methods This was a multi-center, open-labeled, prospective, interventional study. Subjects who had received complete primary dose of DTwP-HB-Hib vaccine from the previous phase III trial were recruited in this trial. Subjects were given one dose of DTwP-HB-Hib (Pentabio®) booster at age 18-24 months old. Diphtheria, tetanus, pertussis, hepatitis B, Hemophilus influenza type B antibodies were measured before and after booster to determine antibody persistence and immune response. Vaccine adverse events were assessed immediately and monitored until 28 days after the booster recorded with parent's diary cards. Results There were 396 subjects who completed the study. Increased proportion of seroprotected subjects from pre-booster to post-booster were noted in all vaccine antigens: 74.5 to 99.7% for diphtheria; 100 to 100% for tetanus; 40.4 to 95.5% for pertussis; 90.2 to 99.5% for hepatitis B; and 97.7 to 100% for Hib. Common systemic adverse events (AEs) were irritability (23.7-25%) and fever (39.9-45.2%). Local AEs such as redness, swelling, and induration were significantly less common in the thigh group (7.7, 11.3, and 7.1%) than in the deltoid group (28.9, 30.7, and 25%) (P < 0.001). Most AEs were mild and resolved spontaneously within three-day follow-up period. Conclusions Booster of DTwP-HB-Hib vaccine at age 18-24 months is required to achieve and maintain optimal protective antibody. The vaccine is safe and immunogenic to be used for booster vaccination. Trial registration NCT02095314 (retrospectively registered, March 24, 2014).